2004 Neighborhood Indicators Summary - (:unkn) unknown (My University, 2004)
This neighborhood indicators report assesses employment, economic and welfare changes based on eleven years of institutional data for nine ZIP codes (53204, 53205, 53206, 53208, 53210, 53212, 53216, 53218, and 53233) designated as target areas for Community Development Block Grant program as in the city of Milwaukee. The 2002 income tax data (based on state tax returns filed by April 2003) provides income earnings data that is three years more current than the 1999 incomes reported by the U.S. Census. Funding for the report was provided by the Greater Milwaukee Foundation and the City of Milwaukee Community Development Block Grant Program. Among the areas addressed are: age of the population, family income and workforce growth, earned income tax credits, working families with income below poverty, child care availability and subsidies, families receiving public assistance, business activity in the neighborhood, housing trends, transportation barriers, and neighborhood safety.
Keywords: neighborhood indicators; family income; crime; public assistance; business trends